Rotary Corn Roaster for Uniform Heat Distribution: Pemanggang Jagung Putar untuk Distribusi Panas yang Merata - Annas Ardiansyah; Ali Akbar (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Corn roasting remains a widely used food processing activity in small-scale culinary businesses, where conventional roasting methods commonly rely on manual operation and uneven heat circulation. Specific Background: Rotary-based roasting technology offers a mechanical solution to support more consistent heating during the roasting process while reducing operator workload. Knowledge Gap: Existing traditional corn roasting practices still depend on manual turning and manual airflow control, resulting in uneven maturity and higher risk of burning. Aims: This study aims to design and evaluate a rotary corn roasting device equipped with three fan units to support stable heat distribution and consistent roasting performance. Results: The developed device utilized a galvanized steel frame, stainless steel rotary cylinder, and integrated gear mechanism for rotary movement. The system accommodated up to nine corns with a maximum average length of 15 cm. The roasting process required approximately 18–20 minutes at a rotary speed of 13 rpm, while the three fans operated with a total electrical power consumption of 18 watts. The rotary mechanism supported more uniform roasting and reduced manual labor during operation. Novelty: The proposed design combines a manual rotary cylinder system with integrated airflow support using three electric fans in a compact corn roasting unit. Implications: This device provides a practical roasting solution for small-scale corn vendors by supporting stable roasting conditions, energy-efficient operation, and more consistent product quality.Highlights: Three integrated fans maintained stable charcoal combustion during roasting. Rotary cylinder mechanism produced consistent maturity on all corn surfaces. Compact roasting unit processed nine corns within 18–20 minutes. Keywords: Corn Roasting; Rotary System; Heat Distribution; Stainless Steel; Food Processing Equipment